Kid sheriff and the terrible Toads - Shea, Bob (Roaring Brook Press, 2014)
The Toad brothers are wreaking havoc in Drywater Gulch when a boy with no experience but immense knowledge of dinosaurs rides into town on his tortoise and declares himself the new sheriff.